Adenovirus-2 mRNA is transcribed as part of a high-molecular-weight precursor RNA. - Bachenheimer, S (1975)
The order of transcription and the length of nascent RNA transcripts from adenovirus-2 (Ad-2) DNA in the nucleus of infected cells has been deduced by labeling the growing RNA chains in vivo for a very brief period, separating the RNA on the basis of size, and hybridizine to the ordered EcoRI restriction endonuclease fragments derived from Ad-2 DNA. The majority of the virus-specific RNA molecules are synthesized as very high-molecular-weight units beginning at a common point at least 25-30,000 base pairs from one end of the Ad-2 DNA. These molecules can be reduced in size without further RNA synthesis. The experiments indicate the obligatory origin of Ad-2 mRNA from a high-molecular-weight precursor molecule.